The Practice of ὀνοματοποιεῖν: Some Peculiar Statements in the Ancient Neoplatonic Commentators on Aristotle - Granata, Daniele (Peitho. Examina Antiqua, 2016)
This paper shows the role of ὀνοματοποιεῖν in Neoplatonism and how this practice is ruled by an onto-logical canon. While ὀνοματοποιεῖν itself means the making of a brand new name, its usage is manifold. As Aristotle explains in Rh. III 2, poets take advantage of ὀνοματοποιεῖν to catch the undefined and give it a recognisable image, by means of a metaphorical name. In science, this practice, codified by Aristotle, is twofold: ὀνοματοποιεῖν meant both to re-semanticize words wellknown and to create names ex novo for things not discovered or studied yet. After analysing ὀνοματοποιεῖν’s recurrence in Aristotle, I illustrate that, according to Neoplatonic Commentators, impositio can be, both natural and technical, only of things in actuality, having a solid consistency. Intermediates between contraries, presumed relatives and powers as qualities are nameless – as Philoponus notices in his In Categorias – since they haven’t an independent status and aren’t definable. This bond between the original rhetorical practice and the ontological perspective, sketched in Int. 1, was strengthened by Alexander, who filled Aristotle’s gaps, stating that names signify things’ being, i.e. the form acquired in actuality.